Prenatal stress impairs recognition memory and leads to neurodevelopmental deficits in hippocampus of adolescent rats with early acute pentylenetetrazole-kindling - Çelik, Kübra; Bilim, Petek; Garip, Gurur; Durmaz, Burak; Y. Sözmen, Eser; Baka, Meral (The European Research Journal, 2021)
Objectives: This study aimed to investigate the effects of prenatal stress (PS) on hippocampus of early acute pentylenetetrazole (PTZ)-kindled offspring in adolescence. Recognition memory, morphological changes and synaptophysin levels in hippocampus were evaluated. Methods: Restraint stress was induced to a group of pregnant dams and non-stressed (NA) group remained undisturbed. Next, male and female offspring were divided as 1. PS-PTZ, 2. PS -control, 3. NA-PTZ and 4. NA-control (n = 12 in each group). The object recognition test was performed following PTZ injection (45 mg/kg) on postnatal day 10 (P10). Brains were collected on postnatal day 35 (P35) to determine neuronal density and synaptophysin expression by immuno/-histological studies. Further, oxidative stress products in hippocampus were analyzed with different biochemical assays. Results: PS impaired recognition memory in PTZ group significantly (p = 0.03); however, the impairment of PS was reversible in control group compared to PTZ (p = 0.04). Furthermore, PS caused neuronal loss in CA1 (p = 0.01) and decreased synaptophysin expression in the CA3 area of hippocampus in PTZ group (p = 0.03). PS also increased the oxidative stress markers in PTZ group significantly (p < 0.05). Conclusions: These results suggest that PS causes neurodevelopmental deficits in adolescent hippocampus and recognition memory after early-life seizures prominently. However, the damage of only PS in adolescence can be reversible. Therefore, the effects of PS in the adult hippocampus and other regions of brain need to be further studied.